Penghinaan dan Pencemaran Nama Baik Sebagai Fenomena Kebebasan Bersosialmedia Dalam Persepektif Cybercrime - Armansyah - (Jatiswara, 2016)
Developments in science and technology can lead to rapid high-techcrime (cybercrime). It is characterizedby the emergence ofvarious forms oftechnological innovation is one of Interconnected Network, popularly referred internet. Libel cases occur as a result of the abuse of freedom of social media can be trapped in addition to Criminal Act (Kitab Undang-Undang Hukum Pidana) and Act Number 11 Year 2008 About Information and Transactions Electronics (UU ITE).